Pengaruh Pendidikan Kewirausahaan terhadap Minat Berwirausaha Mahasiswa Program Studi Pendidikan Ekonomi Universitas Bhinneka PGRI - Ferdiansyah, Mohammad Yusuf Ananwar; Hastuti, Maria Agatha Sri Widayati (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
This study aims to determine the effect of entrepreneurship education on the entrepreneurial interest of students in the Economics Education Study Program at Bhinneka PGRI University. The study employed a quantitative associative approach with a Likert-scale questionnaire as the data collection instrument. The population consisted of eighth-semester students, with a total sample of 90 respondents. The results revealed that entrepreneurship education significantly influences entrepreneurial interest, with a t-value of 5.549 exceeding the t-table value of 1.9861 and a significance level of 0.000 < 0.05. The Adjusted R² value of 0.462 indicates that entrepreneurship education contributes 46.2% to the variation in entrepreneurial interest. These findings emphasize the critical role of entrepreneurship education in fostering students’ interest in entrepreneurship.